Extrato oleoso da polpa de bocaiuva na alimentação de frangos de corte - Perin , Giovana Regina (2021)
This work was developed with the objective of determining the effect of the inclusion of levels of oily extract of bocaiuva pulp (OEB) in the feeding of broilers on zootechnical performance, relative weight of organs, carcass outturn, parameters meat quality and intestinal morphometry. Were used 1.176 broilers distributed in a completely randomized experimental design with seven treatments, with five inclusion levels of OEB -100; 200; 300; 400 and 500 ppm and two controls (negative control - NC, without addition of antibiotic and positive control - PC, with addition of antibiotic), seven repetitions and 24 poultry per experimental unit. The OEB inclusion levels did not influence (P> 0.05) on weight gain (WG), average feed intake and feed conversion (FC). For the contrasts (comparison between diets containing extract, regardless of the level and control diets), it was observed that from 1 to 7 days the poultry that received the CP diet had higher WG (P <0.05) compared to the ones that received NC diets. For this same period, the poultry that received the extract in the diets had higher WG in relation to NC. From 1 to 42 days, those ones that received the extract had worse FC (P <0.05) compared to PC. At 7 days, the poultry that received the NC diet had a greater relative weight of the pancreas (P <0.05) compared to the poultry that received diets containing OEB. For the same period, the poultry that received the extract had a greater (P <0.05) length of the small intestine (SI) compared to those ones that received PC feed. At 21 days, a higher (P <0.05) relative weight of SI was observed for the poultry that received the OEB compared to those that received the NC diet. At 42 days, there was a quadratic behavior (P <0.05) for the relative weight and length of the SI. The inclusion of OEB did not change (P> 0.05) the values of villus height, crypt depth, V: C ratio and absorption area of the animals at 7 and 42 days. At 7 days of age, histomorphometric analysis revealed contrast (P <0.05) between NC: PC and PC: OEB for crypt depth and between NC: PC for the ratio of villus: crypts. For the carcass characteristics, there was a quadratic effect (P <0.05) on wing performance. According to the contrasts, the poultry that fed with diets containing OEB had a lower fillet outturn (P <0.05) compared to PC and NC. Regarding the meat quality analysis, there was a positive linear effect (P <0.05) for Luminosity at 15 minutes post mortem. For the TBARS analysis, there was an effect (P <0.05) in relation to the interval of research days, with the highest oxidation value being found in the analysis realized after 20 days of storage. The inclusion of 100 to 500 ppm of OEB in the diets of broilers did not improve the performance or the characteristics of the carcass and it was not possible to observe the antioxidant effect of the extract.